KUALITAS PELAYANAN PRAMUSAJI DI CINNAMON POOLSIDE RESTAURANT HOTEL D`OXVILLE PADANG - Juita, Mentari Danny; Waryono, Waryono; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
The reseach aims to know the quality of waitres service in Cinnamon Poolside Restaurant Hotel D`oxville Padang review from 5 indicators of quality services which are: reliability, responsiveness, assurance, empathy, and tangibles. The research type is descriptive quantitative. The population of this research are all customers who had eat or drink in Cinnamon Poolside Restaurant Hotel D`oxville Padang with the number of the average guest as much as 621 people. The sampling in this study is purposive sampling as many as 86 people. The data collection are done by questionnaires using the scale of likert and has been tested the validity and reliability. This research result indicates that overall the quality of service in the Cinnamon Poolside Restaurant Hotel D`oxville Padang is good with 56,98% of the respondents declared as good and 34,88% of the respondents declared as enough.